2019
DOI: 10.18203/2349-2902.isj20190412
|View full text |Cite
|
Sign up to set email alerts
|

Typhoid fever colitis with massive lower gastrointestinal bleeding

Abstract: Authors are presenting the case of a 34year old female, with no known comorbidities, who after recent travel to Pakistan, presented with fever for 1 month and was diagnosed with typhoid fever.During her admission she developed bleeding per rectum and abdominal pain labeled as right-side colitis, confirmed by endoscopy and CT scan, which was managed surgically by extended right hemicolectomy and ileostomy.The aim of this case is to discuss a rare complication of typhoid fever which is lower gastrointestinal ble… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Studies reported that these complications are rarely encountered nowadays due to timely and effective antibiotic treatment. 8 , 9 Our patient presented with hematochezia after 2 weeks of systemic symptoms onset. Diagnosis of enteric fever is confirmed by isolation of Salmonella typhi from blood, bone marrow, stool, and urine specimens.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Studies reported that these complications are rarely encountered nowadays due to timely and effective antibiotic treatment. 8 , 9 Our patient presented with hematochezia after 2 weeks of systemic symptoms onset. Diagnosis of enteric fever is confirmed by isolation of Salmonella typhi from blood, bone marrow, stool, and urine specimens.…”
Section: Discussionmentioning
confidence: 81%
“…Life-threatening bleeding requires invasive measures including angiographic coil embolization, endoscopic therapy (adrenaline injection, thermal coagulation, or hemoclipping, alone or in combination), and surgical interventions (hemicolectomy or segmental resection). 6 , 9 , 12 , 14 , 15 …”
Section: Discussionmentioning
confidence: 99%